2014
DOI: 10.4236/ae.2014.21007
|View full text |Cite
|
Sign up to set email alerts
|

Harmonia axyridis Pallas (Coleoptera: Coccinellidae): Biological aspects and thermal requirements

Abstract: The aim of this study was to determine the biological aspects and thermal requirements of Harmonia axyridis Pallas (Coleoptera: Coccinellidae) fed daily with Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) eggs. Under laboratory conditions, the experiment was carried out in acclimatized chambers set to 18˚C, 21˚C, 24˚C, 27˚C, and 30˚C. Larvae of H. axyridis were separated, kept in a glass tube, and fed with A. kuehniella eggs. The Asiatic lady beetle adults were separated into 20 couples and kept in plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…The shorter development duration of preadult and adult H. axyridis at higher temperatures (i.e., 30 °C) is most likely due to increased attack and metabolic rate in response to increased food consumption and energy requirements, allowing the predator to rapidly advance to the next stage. The mean longevities of male and female adults also prolonged at 15 °C and reduced with warming temperatures, in accordance with De Oliveira Ramos, et al 60 , who under similar thermal conditions reared H. axyridis on different prey, Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae). de Castro-Guedes, et al 33 reported that female H. axyridis could survive on average 91.13 ± 25.53 d on the eggs of A. kuehniella at 25 °C.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The shorter development duration of preadult and adult H. axyridis at higher temperatures (i.e., 30 °C) is most likely due to increased attack and metabolic rate in response to increased food consumption and energy requirements, allowing the predator to rapidly advance to the next stage. The mean longevities of male and female adults also prolonged at 15 °C and reduced with warming temperatures, in accordance with De Oliveira Ramos, et al 60 , who under similar thermal conditions reared H. axyridis on different prey, Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae). de Castro-Guedes, et al 33 reported that female H. axyridis could survive on average 91.13 ± 25.53 d on the eggs of A. kuehniella at 25 °C.…”
Section: Discussionsupporting
confidence: 87%
“…Coccinellidae are shown to reproduce even more on non-aphid preys in some studies, which demonstrates the importance of alternative resource 58 , 59 . Eggs of lepidopterans were the best diet for H. axridis because shorter duration and higher survival of the larval stage of this predator was evident on the eggs 34 , 60 . Abdel‐Salam and Abdel‐Baky 34 estimated the R 0 of H. axyridis when feeding on frozen and fresh eggs of the Sitotrega cerealella , and showed moth eggs to be a better diet based on findings obtained by applying the female age-specific life table and adult age.…”
Section: Discussionmentioning
confidence: 99%
“…The higher survival of eggs of H. axyridis at low temperatures probably provides a fitness advantage during the cold season (Castañeda et al, 2005). However, the lower survival of eggs at higher temperatures observed in H. axyridis and other ectotherms (Huang et al, 2008;Radchuk et al, 2013;Zhang et al, 2013;Oliveira Ramos et al, 2014;Benelli et al, 2015) may limit populations during summer or in hot regions. In agreement with this, a recent review of the worldwide distribution of H. axyridis confirms that this species is scarce in tropical countries and in desert regions (A.…”
Section: Discussionmentioning
confidence: 93%
“…The high survival rates and fast growth rates of invasive alien species may help them to succeed in competition with native species under global change scenarios (Whitney-Johnson et al, 2005;Mainka & Howard, 2010;Radchuk et al, 2013;Oliveira Ramos et al, 2014). Moreover, with global warming, the physiological performance of native and invasive alien species and the persistence of their populations may also change (Folguera et al, 2009;Bozinovic et al, 2011a,b).…”
Section: Introductionmentioning
confidence: 91%
“…Both species feed primarily on aphids and are frequently found on the same plants. In South Africa, H. axyridis has a critical thermal maximum of ~44 °C (Shinner et al 2020), and from data gathered in other regions, its development, fecundity and survival typically decline at temperatures above 30 °C (de Oliveira Ramos et al 2014;Zhang et al 2014;Barahona-Segovia et al 2016;Roy et al 2016). Most of this species' life-history traits have optimal temperatures between 20 and 25 °C (Suppl.…”
Section: Study Species and Field Collectionsmentioning
confidence: 99%